2013
DOI: 10.1590/s0100-204x2013000800018
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade em armazenamento da carne de tilápia-do-nilo mecanicamente separada, lavada, adicionada de conservantes e congelada

Abstract: Resumo -O objetivo deste trabalho foi avaliar a influência do processo de lavagem e da adição de eritorbato de sódio e tripolifosfato de sódio na estabilidade de carne mecanicamente separada (CMS), obtida a partir de resíduos da filetagem de tilápia-do-nilo (Oreochromis niloticus). Foram avaliados quatro tratamentos, em triplicata: CMS, lavada ou não e armazenada, com ou sem a adição de conservantes, durante 180 dias de armazenamento a -18ºC. Para a avaliação da estabilidade, foram realizadas análises microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
(14 reference statements)
2
5
1
3
Order By: Relevance
“…All minces reported TVB-N values lower than the official permitted limits (30 to 35 mg N/100 g). Unlike the present study, previous reports observed an increase of BVT-N content (80%) in frozen tilapia fillets during storage (Emire & Gebremariam, 2009) and 33% after the 60 th day of tilapia-sketelon mince freezing storage (Kirschnik et al, 2013). Peroxide values for washed mince were not determined due to its low lipid content.…”
Section: Physicochemicalcontrasting
confidence: 99%
See 3 more Smart Citations
“…All minces reported TVB-N values lower than the official permitted limits (30 to 35 mg N/100 g). Unlike the present study, previous reports observed an increase of BVT-N content (80%) in frozen tilapia fillets during storage (Emire & Gebremariam, 2009) and 33% after the 60 th day of tilapia-sketelon mince freezing storage (Kirschnik et al, 2013). Peroxide values for washed mince were not determined due to its low lipid content.…”
Section: Physicochemicalcontrasting
confidence: 99%
“…Regarding ash content (Table 1) the registered value in M was 0.7±0.2 which is comparable to previous reports for tilapia-skeleton mince (0.9-1.1%) (Oliveira et al, 2012;Kirschnik et al, 2013). However, 70% of the ash content (p < 0.05) was removed through the washing process, which is considerably higher than the removal achieved (29-40%) by other authors for Tilapia-skeleton mince (Oliveira et al, 2012;Kirschnik et al, 2013).…”
Section: Physicochemicalsupporting
confidence: 88%
See 2 more Smart Citations
“…The nutritional characteristics of MSM show great variation as the result of variations in its production process. Kirschnik and Macedo-Viegas (2009); Freitas et al (2012); Kirschnik et al (2013); Fogaça et al (2015) report varying values in moisture (62.17 to 79.84%), crude protein (9.75 to 15.87%), lipids (2.91 to 18.81%), and mineral matter (1.00 to 2.11%). Nevertheless, the transformation of these residues into products for human consumption is a great alternative for the utilization of tilapia residues (Vidal et al, 2011;Freitas et al, 2012), besides reducing the deposition of organic waste in the environment improving the concept of sustainability (Magalhães et al, 2019), as occurs in other productive chains of chickens, pigs and cattle (Lustosa-Neto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%